Interior Design of Public and Accommodation Spaces for A 5000 GT Ferry Ro-Ro - Wira Setiawan; Muhammad Yogi Raditya; Husein Syahab (Institut Teknologi Sepuluh Nopember, 2022)
Currently in Indonesia, the need for maximum service in terms of passenger transportation on ships needs to be increased in order to compete with other modes of transportation such as airplanes and trains. The lack of customer satisfaction is caused by several factors such as the condition of the facilities and the comfort of the passengers on the trip. The quality of the facilities and services of the passenger ship can be improved by redesigning the interior of the public facilities and accommodation space for the passengers of the ship. The interior design is carried out to increase public interest in using the services of the ferry. Based on the results of a survey of ship passengers' opinions, it is known that passenger comfort can be improved, especially on the factors of cleanliness, room arrangement, air circulation, rejuvenation of the room as well as interior visuals that are made more attractive. The result of conceptualizing and designing the interior of the ship is that it is necessary to have an interior design that is popular with the public, has its own characteristics, attracts public attention, and is simple and not shabby design. The design concept that fits the needs above is the Avant basic concept because this design theme is a translation of current design trends and presents its own characteristics for the ship. Interior rearrangements and furniture adjustments were made according to the activities on the ship and adjusted to the passenger comfort factor according to marine standards while taking into account the statutory regulations.